Effects of a dietary strawberry powder on parameters of vascular health in adolescent males. Issue 4 (20th June 2016) - Djurica, Dragana; Holt, Roberta R.; Ren, Jingyan; Shindel, Alan W.; Hackman, Robert M.; Keen, Carl L.
Abstract: Previous studies have shown that the intake of freeze-dried strawberry powder (FDSP) improves select markers of cardiovascular health in adults with cardiovascular risk factors; however, whether these improvements can be observed in at-risk adolescents is unknown. A randomised, double-blind, cross-over study enrolled twenty-five overweight or obese males, aged 14–18 years, to consume 50 g of a FDSP or a control powder, daily for 1 week. Before and after each test period, measures of microvascular function, plasma nitrate/nitrite, platelet reactivity and blood lipids were collected at baseline and acutely 1 h after FDSP intake. Acute plasma nitrate/nitrite levels increased 1 h after consuming the FDSP during Study Visit 1 before daily FDSP intake ( P <0·001) and during Study Visit 2 after 1 week of FDSP intake ( P <0·001) compared with control powder intake. As a group, fasting nitrate/nitrite levels did not significantly change after 1 week of control or FDSP intake. However, for those individuals where fasting nitrate levels increased after short-term FDSP intake compared with controls, an increase in reactive hyperaemia index (RHI) was observed ( P =0·014), whereas RHI was unchanged in those individuals who did not have a significant increase in nitrate ( P =0·396). Taken together, these data support the concept that strawberries can provide vascular health benefits to heavier adolescent males.